Contamination of fish in UK fresh water systems: Risk assessment for human consumption. (March 2015) - Rose, Martin; Fernandes, Alwyn; Mortimer, David; Baskaran, Christina
Graphical abstract: Highlights: Unmanaged inland water-ways may be more polluted than seas or water used for aquaculture. Concentrations of a wide variety of contaminants in freshwater fish are given. Consumption of fish caught as a result of leisure activities is increasing. Inland waters may be contaminated due to geological or anthropogenic consequences. Abstract: There is growing evidence that more people in the UK are consuming fish taken from inland waterways. This may be partly due to the increased numbers of migrants from Eastern Europe where this is part of traditional culture and partly because of a desire to try new foods encouraged by celebrity chefs. Fish can bioaccumulate environmental contaminants and so could contribute a significant amount to dietary exposure to these chemicals. This study examined the changing habits of anglers and consumers and characterised a range of existing and emerging contaminants in freshwater fish species with a view to determining current levels of occurrence and possible risk from consumption. The project was conducted in two stages. The first stage included (a) a study that identified freshwater systems that are contaminated either by anthropogenic activity or as a result of the geology of the area; and (b) socioeconomic research to assess the consumption habits of the public, particularly anglers, with respect to fish and shellfish from unmanaged inland waterways. Based on the outcome from the first stage, specific rivers and other inland waterways were chosen for investigation, along with the range of contaminants to be included in the analytical programme. Predicted contamination levels and prevalence of anglers were among the factors taken into consideration. The second stage of the project involved sampling and analysis of fish taken from selected locations on the chosen waterways. A range of fish species from a variety of inland water habitats were obtained. These were analysed for the following contaminants: heavy metals, chlorinated dioxins (PCDD/Fs), polybrominated biphenyls (PBBs), polychlorinated biphenyls (PCBs), brominated dioxins (PBDD/Fs), polychlorinated naphthalenes (PCNs), polybrominated diphenylethers (PBDEs), OC pesticides, organotin compounds and organo-fluorine compounds. Legal limits for contaminants apply only to food traded commercially, but some samples were in excess of the regulatory limits for PCDD/Fs and PCBs in such fish. The maximum detected WHO-TEQ (1998) for PCDD/Fs plus PCBs was over 32 ng kg −1 on a whole weight basis for a sample of barbel from the River Don, and 6 other samples were also above the 8 ng kg −1 limit.